Negotiations between Milovanović and Geshov in the Creation of the Balkan Alliance in 1912 - Stanojević, Saša D. (Collection of Papers of the Faculty of Philosophy in Priština, 2020)
Years before the First Balkan War 1912/13 marked by intense diplomatic activities aimed at creating alliances between Serbia, Bulgaria, Greece and Montenegro. Its goal was the liquidation of Ottoman rule in the territory of the so-called European Turkey, the liberation of compatriots from centuries-old occupation and the return of the territory to their countries of origin. The Serbian-Bulgarian agreement formed the basis of a broader alliance. It was established primarily through agreements between two prominent statesmen – Milovan Milovanović and Ivan Evstratiev Geshov, who at the final stage of negotiations were simultaneously prime ministers and foreign ministers. The results of the negotiations were translated into an interstate agreement with a secret annex of March 13, 1912. Despite the great temptations that followed the creation of the Serbian-Bulgarian agreement, Milovanović and Geshov still managed to bring the whole process to a successful end. The great powers persistently insisted on maintaining the status quo in the Balkans, which did not favor the Allies policy. The Alliance, however, was most concerned with the Ottoman Empire, according to which its blade was pointed. Unable to do anything more, neighborhood events were followed here with the utmost care and readiness. The first step in the Allies intention was the rapid and effective liquidation of Ottoman rule in the Peninsula, which for many who doubted the Allies resolve was an unexpected turn of events. However, when the burning question about the partition of this space came to the fore, the fate that many feared could not be avoided. Those who were in Bulgaria for further compromise with the Allies were not favorably regarded there by radical circles close to King Ferdinand and Austro-Hungary. Because of this, Geshov also had to withdraw from the political scene by resigning. Milovanovic passed away earlier. In all likelihood, an alliance without the famous duo who for the most part created it could not survive.